The Influence Profitability, Financial Leverage, and Firm Size on Income Smoothing Empirical studies on banking companies listed on stock exchanges in Indonesia 2009-2012 - Muhammad Taufik; Haryetti '; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to examine profitability, financial leverage, and firm size, on income smoothing in banking companies listed in Indonesia Stock Exchange 2009-2012. This study uses income smoothing as the dependent variable, the independent variable we use profitability, financial leverage, and firm size. Purposive sampling method we used to get the sample, and from 32 firms that we observed, we got 19 firms as the samples. To analize the data Multiple Linier Regression, F-test and t-test analysis are used SPSS 20. The results shows that the information profitability, financial leverage, and firm size variables simultaneously have significant effect on income smoothing. Meanwhile partially, Profitability has negative significant effect on income smoothing, financial leverage has positive significant on income smoothing and firm size has positive significant effect on income soothing.Keywords: Profitability, Financial Leverage, Firm Size and Income Smoothing